Implementasi Permainan Tradisional Ular Naga untuk Menstimulasi Sikap Kerja Sama Anak Usia Dini di TK PKK Lestari Sumberkatimoho Krejengan Probolinggo - Wiwin Indah Qomariyah; Ismatul Izzah; Ivonne Hafidlatil Kiromi (Universitas Islam Lamongan, 2026)
This study was motivated by the importance of developing cooperation skills in early childhood through enjoyable and meaningful play activities. The study aimed to describe the implementation process of the traditional Snake and Dragon game in developing cooperation skills among early childhood children at TK PKK Lestari Sumberkatimoho Krejengan. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of 16 children in Group B and the classroom teacher at TK PKK Lestari Sumberkatimoho Krejengan. Data were collected through interviews, observations, and documentation. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings showed that the implementation of the traditional Snake and Dragon game was able to develop children’s cooperation skills through activities such as forming lines, supporting each other, following instructions, and adjusting movements with peers in the group. Based on the observation results, 75% of the children achieved the categories of Developing as Expected (BSH) to Very Well Developed (BSB) in the observed cooperation indicators. Children learned not to act individually but to maintain group cohesion so that the game could run effectively. In addition, the game also fostered responsibility and self-confidence according to each child’s role in the group. Therefore, the traditional Snake and Dragon game can be used as an effective learning strategy to develop cooperation skills in early childhood.